The Effect of Leverage, Liquidity, and Size on Profitability In Food and Beverage Sub-Sector Companies Listed On The IDX 2019 - 2022 - Prasetyo, Fikri Hilya; Isbanah, Yuyun (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
The purpose of this research is to determine the effect of leverage, liquidity, and company size on profitability. The sample in this study were food and beverage sub-sector companies listed on the IDX with the number of samples to be used in this study totaling 64 companies. Determination of the sample in this study using purposive sampling. Data analysis used classic assumption tests and multiple linear analysis. The results of this study indicate that liquidity has no significant effect on profitability, company size has no significant effect on profitability, and leverage has a negative and significant effect on profitability in food and beverage sub-sector companies listed on the IDX during the 2019-2022 period. So it can be concluded that only leverage has a significant effect on profitability in the Food and Beverage sub-sector listed on the IDX in 2019-2022.